KOMPETENSI SOSIO KULTURAL UNTUK JABATAN PIMPINAN TINGGI PRATAMA ESELON II.B DILINGKUNGAN PEMERINTAH ACEH - Munawar, Munawar (FITRAH: International Islamic Education Journal, 2019)
The socio-cultural competencies stipulated in Permenpan-RB Number 38 Year 2017 have not accommodated the characteristics and needs of the Aceh Government. The competencies of the Aceh Government Apparatus must be in harmony with the Islamic Shari'a and socio-cultural aspects of Aceh. Competency development of the Aceh Government Apparatus needs to be oriented towards the establishment of HR Islamic Apparatus, especially having the value of socio-cultural competencies based on Islamic education.The problems examined in the context of developing socio-cultural competencies for the Primary Government (JPT) of the Primary Government of Aceh are: (a) What is the competency in managing the cultural environment based on Islamic education; (b) How competence builds a social network based on Islamic education; (c) What is the value of social empathy competence based on Islamic education; (d) What are the gender and diffable sensitivity competencies based on Islamic education. This study uses a qualitative approach. Data was collected through in-depth interviews, FGDs and documentation studies. Informants were selected by purposive technique and snowball sampling. Key informants are officials who have duties and authority to develop HR competencies. Checking credibility and data analysis is done using triangulation techniques. The development of value-based socio-cultural competencies in Islamic education for the JPT Primary echelon II.b was formulated at an advanced level. The results of developing socio-cultural competencies in question are: (a) Competence in managing the cultural environment for JPT Pratama II.b is described as the ability to utilize cultural differences constructively and creatively to improve organizational effectiveness as a form of worship. (b) Social network competencies for JPT Pratama II echelon.b are described in the formulation of the profesonalization and transformation of government communications to increase public trust and participation; (c) Social empathy competency for Primary JPT echelon II.b is described as the ability to carry out prosocial behavior; (d) Gender and disability sensitivity competencies for JPT pre-echelon II.b are described as the ability of gender mainstreaming and the utilization of the lives of diffable groups.